2014
DOI: 10.1016/j.freeradbiomed.2014.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic antioxidant AEOL 10150 treatment ameliorates sulfur mustard analog 2-chloroethyl ethyl sulfide-associated cutaneous toxic effects

Abstract: Our previous studies and other published reports with the chemical warfare agent sulfur mustard (SM) and its analog 2-chloroethyl ethyl sulfide (CEES) have indicated a role of oxidative stress in skin injuries caused by these vesicating agents. We examined the effects of the catalytic antioxidant AEOL 10150 in attenuation of CEES-induced toxicity in our established skin injury models (skin epidermal cells and SKH-1 hairless mice) to validate the role of oxidative stress in the pathophysiology of mustard vesica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…Our results are also in agreement with previous demonstration of efficacy of this compound against expression of inflammatory markers in a rat model of 2-chloroethyl ethyl sulfide (CEES)- induced lung injury (O’Neill et al, 2010), a mouse model of stroke (Bowler et al, 2002) and mouse model of chlorine-induced lung injury (McGovern et al, 2011). Additionally, these studies also demonstrated the efficacy of the antioxidant in inhibiting oxidative stress (Castello et al, 2008; O’Neill et al, 2010; Tewari-Singh et al, 2014). We confirmed its antioxidant action in the pilocarpine model using the tissue samples from the same rats that were utilized for the multiplex cytokine analysis, indicating that the effect of the compound on inflammation is most likely due to its effect on oxidative stress, confirming target engagement by the drug.…”
Section: Discussionmentioning
confidence: 83%
“…Our results are also in agreement with previous demonstration of efficacy of this compound against expression of inflammatory markers in a rat model of 2-chloroethyl ethyl sulfide (CEES)- induced lung injury (O’Neill et al, 2010), a mouse model of stroke (Bowler et al, 2002) and mouse model of chlorine-induced lung injury (McGovern et al, 2011). Additionally, these studies also demonstrated the efficacy of the antioxidant in inhibiting oxidative stress (Castello et al, 2008; O’Neill et al, 2010; Tewari-Singh et al, 2014). We confirmed its antioxidant action in the pilocarpine model using the tissue samples from the same rats that were utilized for the multiplex cytokine analysis, indicating that the effect of the compound on inflammation is most likely due to its effect on oxidative stress, confirming target engagement by the drug.…”
Section: Discussionmentioning
confidence: 83%
“…However, one needs to keep in mind that the CEES toxicity depends on specific conditions of the treatment protocol. The studies of CEES induced cytotoxicity in HaCaT cells reported LC50 values differing by at least one order of magnitude within a range of 0.25 to 2 mM depending on treatment time and conditions applied (Paromov et al, 2011a,b;Tewari Singh et al, 2010, 2014a.…”
Section: Mustards Exhibit Substance Specific Cytotoxicity Profilesmentioning
confidence: 99%
“…Catalytic antioxidants can scavenge multiple reactive oxygen and nitrogen species without being consumed in the reaction (Day, 2004). This antioxidant has shown promising effects in other studies of SM induced toxicity in both in vitro and in vivo models (Gould et al, 2009;O'Neill et al, 2010O'Neill et al, , 2011Tewari-Singh et al, 2014). This catalytic antioxidant has also displayed therapeutic benefits in other models of lung injury such as exposure to fractionated radiation and chlorine gas inhalation (McGovern et al, 2011;Rabbani et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…AEOL 10150 is a metalloporphyrin class of catalytic antioxidants that has shown promising therapeutic potential for suppressing oxidative stress in relevant SM analog, 2-chloroethyl ethyl sulfide (CEES) models (Gould et al, 2009;O'Neill et al, 2010O'Neill et al, , 2011Tewari-Singh et al, 2014). The aim of this study is to characterize the efficacy of this catalytic antioxidant in improving survival by attenuating the progression of oxidative stress, inflammation, and injury following SM inhalation.…”
mentioning
confidence: 99%